СИСТЕМА ЛЕЙТМОТИВОВ В СБОРНИКЕ ИОСИФА БРОДСКОГО НОВЫЕ СТАНСЫ К АВГУСТЕ - СНЕЖАНА КРЫЛОВА (Studia Rossica Posnaniensia)
The article is devoted to semantic interpretation of characteristic motifs in the collection of Joseph Brodsky’s poetry New Stanzas to Augusta (Новые стансы к Августе). Deep analysis of recurring poetic image, such as ghost, the motif of light and shadow, and most of all the motif of time, reveals the complicated web of interrelations and the evolution of “common places”. It makes the author ascertain that the poems in the collection (and all poet’s works) can be treated as one text.